River crossings as principal points of human/reindeer relationship in Eurasia - Baskin, Leonid M. (Rangifer, 2003)
Since prehistoric time, indigenous peoples throughout Eurasia have hunted reindeer from boats when the animals were swimming across rivers. A number of landscape peculiarities and reindeer behavior features determine the phenomena of mass reindeer river crossings at a few points. Hunting at river crossings occurs predominantly in the autumn season along migration routes of tundra and forest-tundra populations. In the past, many of the well-known river cross¬ings were in private possession by indigenous families (Anonymous, 1945). In northern Russia, since the 1970s, the reindeer river crossings became the place of commercial slaughter of reindeer. The state hunting husbandry "Taymyrsky" was established, it received licenses for hunting and then totally regulated who was permitted to hunt reindeer and where (Sarkin, 1977). Step by step, most of the indigenous peoples have been forced out of their traditional hunting locations by aggressive non-indigenous newcomers and became unemployed. Large-scale commercial hunting has led to overexploitation and the decline of reindeer populations in Yakutia and Taymyr. The sustainable use of migratory reindeer populations, as well as renaissance of hunting economies, are possible if exclusive use of some of the reindeer river crossings are returned to indigenous communities as their property, with others to be used by urban hunters and commercial enterprises under the improved state regulations and enforcement.